Determinism, Probability and Theories of Science - Nekrašas, Evaldas (Problemos, 1972)
The conception of ontological determinism is being analysed in the article. Articulation of a system depends on the activity of the investigator. This is why the assertions about the world’s structure which disregard such an activity can hardly be attached sense to. Besides the theory of integral determinism can be found fault with as it presupposes the unified language to the description of the world and substantiality of time. The paper gives proof to the following thesis: probabilistic and strongly deterministic descriptions of the objects are compatible if probability is interpreted empirically.